Combining Ideas and Artifacts: An Interaction-Focused View on Computing Education Using a Cybersecurity Example - Terfloth, Lutz; Budde, Lea; Schulte, Carsten
In this paper, we present a novel approach to design teaching interventions for computing education, elaborated using an example of cybersecurity education. Cybersecurity education, similar to other computing education domains, often focuses on one aspect and separate themselves from the other approach. In other words, they focus on one of the two different aspects: a) either teaching how to use and to behave, or b) how technology works. Here we suggest another point of focal awareness for teaching – interaction – that allows the recombination of both approaches in a novel way, leading to a reconstruction of the teaching and learning content in a way that – as we hope – supports an understanding on a higher level and thus gives the chance to better develop agency. For this didactic reconstruction of teaching content, we use an approach called the hybrid interaction system framework. In cybersecurity training, teaching interventions oftentimes are in a way successful but seem to not lead to long-lasting changes towards secure behavior. Using simply password security as an example, we show how this new approach recombines the two different priory mentioned teaching approaches in a novel way. Within this short paper, we present our current research progress, discuss potentials and values of the approach in general, and by way of example. Our intention of this submission and early disclosure is to spark discussion and generate further insights especially regarding the following question: What implications does the hybrid interaction system approach have on learning scenarios?